Immunosenescence‐associated microRNAs in age and heart failure. (April 2013) - Seeger, Timon; Haffez, Fatima; Fischer, Ariane; Koehl, Ulrike; Leistner, David M.; Seeger, Florian H.; Boon, Reinier A.; Zeiher, Andreas M.; Dimmeler, Stefanie
<x xml:space="preserve">Abstract</x> Aims Ageing of the immune system, immunosenescence, is characterized by impaired lymphopoiesis, especially B‐lymphocyte maturation, and is a hallmark of chronic heart failure (CHF). MicroRNAs (miRNAs) are non‐coding, small RNAs, which post‐transcriptionally control gene expression of multiple target genes. The miR‐181 family is known to control haematopoietic lineage differentiation. Here, we study the role of the miR‐181 family in immunosenescence and CHF. Methods and results We conducted a clinical study analysing peripheral blood (PB) for miRNA expression and leucocyte distribution of young healthy controls (25 ± 4 years; n = 30), aged healthy controls (64 ± 5 years; n = 13), and age‐matched CHF patients (64 ± 11years; n = 18). The expression of miR‐181 family members was reduced, whereas miR‐34a was increased in PB of aged individuals. In particular, miR‐181c was further reduced in age‐matched CHF patients. In PB, we observed reduced numbers of lymphocytes, in particular cytotoxic T cells and B cells, with rising age, and the expression of miR‐181 correlated with the number of B cells. Notably, in CHF patients, ischaemic heart failure was associated with a further reduction of total B cells as well as their subpopulations, such as memory B cells, compared with age‐matched healthy volunteers. Conclusions Ageing‐ and CHF‐associated changes in PB leucocyte subsets are paralleled by alterations in the expression of miRNAs involved in lymphopoiesis, which might play an important role in the age‐related and CHF‐mediated dysregulation of immune functions resulting in immunosenescence. Furthermore, miR‐181c may serve as a marker for reduced immune functions in CHF patients.